Pasien gagal ginjal kronik TELEHEALTH PADA PASCA RAWAT PASIEN GAGAL GINJAL KRONIK (LITERATURE REVIEW) - Rasmiati Rasmiati; Sigit Mulyono (Poltekkes Kemenkes Kalimantan Timur, 2021)
One of the rapidly growing health technologies today is Telehealth. Telehealth can assist patients in performing self-care, diet management, and monitoring treatment programs while at home. The purpose of this literature review is to describe the use of telehealth in patients with chronic kidney failure. The method used is an electronic data base from journals that have been published through Science Direct, Sage Publications, and PubMed, obtained several articles in the first stage of the search, then focused on the literature using a randomized controlled trial, case control and quasi-experimental design, in order to obtain 16 articles that are ready to be reviewed. Through telehealth nurses can provide holistic and sustainable post-treatment nursing care that will improve the quality of life of patients with chronic kidney failure. In conclusion, the ease of providing information and overcoming the limitations of distance are the advantages of telehealth service, so there is a need for legal aspects, financing and supporting infrastructure so that this remote technology can be useful for patients with chronic kidney failure. Keywords: Telehealth, Quality of Life, Chronik Kidney Disease